2024
DOI: 10.1001/jamaoncol.2023.6277
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy or Chemoimmunotherapy in Older Adults With Advanced Non–Small Cell Lung Cancer

Yoko Tsukita,
Takehiro Tozuka,
Kohei Kushiro
et al.

Abstract: ImportanceImmune checkpoint inhibitor (ICI) plus chemotherapy combination treatment (ICI-chemotherapy) is now a standard treatment for non–small cell lung cancer (NSCLC) without targetable oncogene alterations, but there are few data on ICI-chemotherapy for patients 75 years and older.ObjectiveTo inform the choice of first-line drugs in clinical practice and assess the safety and efficacy of ICI-chemotherapy combination treatment in older adult patients with previously untreated advanced NSCLC.Design, Setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Immune checkpoint inhibitors (ICIs) have emerged as indispensable frontline therapies to manage advanced or recurrent NSCLCs without druggable mutations [ 4 ]. However, considering the age-associated immunosenescence, confirming ICI efficacy in elderly patients is necessary, and several studies have provided valuable insights [ 5 , 6 , 7 , 8 ]. Moreover, ICIs cause a unique array of adverse effects, termed immune-related adverse events (irAEs), wherein reinvigorated immune responses may inadvertently target healthy organs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoint inhibitors (ICIs) have emerged as indispensable frontline therapies to manage advanced or recurrent NSCLCs without druggable mutations [ 4 ]. However, considering the age-associated immunosenescence, confirming ICI efficacy in elderly patients is necessary, and several studies have provided valuable insights [ 5 , 6 , 7 , 8 ]. Moreover, ICIs cause a unique array of adverse effects, termed immune-related adverse events (irAEs), wherein reinvigorated immune responses may inadvertently target healthy organs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morinaga et al conducted a real-world clinical study and observed that the irAE profile remained consistent across age groups [ 7 ]. However, Tsukita et al reported that combining ICI with chemotherapy in patients aged ≥75 years did not confer survival benefits and was associated with an increased incidence of grade ≥3 irAEs compared to ICI monotherapy [ 8 ]. Thus, information on irAEs in the elderly population remains unclear, and accumulating evidence in real-world clinical settings is necessary.…”
Section: Introductionmentioning
confidence: 99%